2006
DOI: 10.2353/ajpath.2006.060445
|View full text |Cite
|
Sign up to set email alerts
|

Teratogen-Induced, Dietary and Genetic Models of Congenital Diaphragmatic Hernia Share a Common Mechanism of Pathogenesis

Abstract: Congenital diaphragmatic hernia (CDH) is a frequently occurring, major congenital abnormality that has high mortality and significant morbidity in survivors. Currently, the pathogenesis of CDH is poorly understood. In this study, we have compared the anatomical characteristics of diaphragm defects in the well-described nitrofen model with the pathogenesis of CDH in vitamin A-deficient rats and wt1 null-mutant mice, representing teratogen-induced, dietary and genetic models of CDH, respectively. Our histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 36 publications
4
106
0
3
Order By: Relevance
“…In cases of Bochdalek CDH, which is the most frequent presentation of CDH, incomplete formation of the posterolateral diaphragm allows invasion of the abdominal contents into the thoracic cavity, impeding lung development (32,65). The pathogenesis of CDH is poorly understood; however, recent research using different animal models of the disorder is beginning to provide insight into its embryonic origins (13,22,23). Equally, progress is also being made in understanding the etiology of CDH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of Bochdalek CDH, which is the most frequent presentation of CDH, incomplete formation of the posterolateral diaphragm allows invasion of the abdominal contents into the thoracic cavity, impeding lung development (32,65). The pathogenesis of CDH is poorly understood; however, recent research using different animal models of the disorder is beginning to provide insight into its embryonic origins (13,22,23). Equally, progress is also being made in understanding the etiology of CDH.…”
mentioning
confidence: 99%
“…Muscle precursor cells (MPC) that form the complete musculature of the diaphragm first migrate to the PPF, and it is also the target for pioneer axons of the phrenic nerve that provides the diaphragm with its nervous input (10,29). With regard to CDH, abnormal PPF development has been shown to underlie diaphragmatic hernia in nitrofen-treated rats, vitamin A-deficient rats, and Wt1-null mutant mice (6,23). Furthermore, analyses of human CDH postmortem tissue have generated data consistent with primary PPF defects (23).…”
mentioning
confidence: 99%
“…CDH is occurred due to the defect of the amuscular component of the primordial diaphragm 6 . The defect causes visceral herniation to fetal thorax and may influence the normal development of the lungs, the bronchi and pulmonary arteries to result in potential pulmonary hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Genes affecting PPF development are COUP-TFII, FOG2, GATA-4, WT1 and Disp1, expressed in the non-muscular mesenchymal components of the diaphragm (Clugston et al, 2006;Clugston et al, 2008;Kantarci et al, 2010). Disp 1 is expressed in the primordial pleuroperitoneal fold (PPF), in diaphragmatic tissues and in the developing lung mesothelium, epithelium, and mesenchyme (Kantarci et al, 2010).…”
Section: Etiologymentioning
confidence: 99%
“…Pathological studies have demonstrated defects in the formation of the primordial pleuroperitoneal folds (PPF) in WT1 null mice (Clugston et al, 2006).…”
Section: Wt1-opathiesmentioning
confidence: 99%